NGARUH PROMOSI KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN NON MEDIS PADA RUMAH SAKIT IBU DAN ANAKERIA BUNDA PEKANBARU - Anisa Tariyeni; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much promotion and workload on performance of non medical employee. Sampels in this study were taken as many as 69 respondens and techniques used census sampling approach. The data in this study using survey method through questionnares filled by non medical employee. Data were obtained by using simple regression analysis dan multiple regression analysis. The result of this study show that promotion has a significant impact on non medical employee’s performance. workload has a significant impact on non medical employee’s performance. And then simultaneously promotion and workload have a significant impact on non medical employee’s performance. Subsequent research is suggested to use other methods in researcing non medical employee’s performance, for example through in-depth interviews of respondents.Keywords: Promotion, Workload, And Employee’s Performance